1988
DOI: 10.1046/j..1988.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Family therapy training research: systems model and review

Abstract: This paper proposes that a systems approach to the organization of family therapy training courses would be advantageous to trainers and researchers alike. A family therapy training programme development model is outlined. Using the stages of this model as a framework, the research into family therapy training is reviewed. The field still remains in its infancy and the quantity of research is relatively sparse. Developments have, however, been made and these auger well for the future. IntroductionRecent years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Previous reviews in this field (Avis and Sprenkle, 1990;Gurman, 1979, 1988;Street, 1988) have been noted by Liddle (1991) to have jointly articulated the research agenda for training and supervision. This agenda has however been based on a rather narrow view of research, namely one that is empirically oriented and residing within a logico-scientific approach; it has not directly embraced a critical perspective.…”
Section: Earlier Key Findings and Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reviews in this field (Avis and Sprenkle, 1990;Gurman, 1979, 1988;Street, 1988) have been noted by Liddle (1991) to have jointly articulated the research agenda for training and supervision. This agenda has however been based on a rather narrow view of research, namely one that is empirically oriented and residing within a logico-scientific approach; it has not directly embraced a critical perspective.…”
Section: Earlier Key Findings and Reviewsmentioning
confidence: 99%
“…The papers published in this field since this author's previous review (Street, 1988) will be included.…”
Section: Bibliography and Critiquementioning
confidence: 99%
See 1 more Smart Citation
“…It was important that those training workshops be evaluated for their effectiveness and efficiency in transferring systemic conceptualization to the trainees (Avis & Sprenkle, 1990;Street, 1988). Therefore, there is a need for valid and reliable instruments to track changes in trainees' level of systemic conceptualization.…”
mentioning
confidence: 99%
“…Street’s (1988) review categorized existing research into personnel studies (related to characteristics of students and trainers); context studies (connected with the setting in which training is offered or graduates are expected to practice); theoretical model studies (concerned with choices about which models are taught); skills studies (investigation of skills to be taught); methodology studies (investigating teaching methods employed); studies of student changes during training ; and therapy outcome studies (related to families treated by the student). He concluded that the main advance in the preceding decade had been the development of measures to assess student changes during training.…”
mentioning
confidence: 99%